Seismic Classification of Selected Sites Base on Dynamical and Geotechnical Properties for Karbala City, Iraq - Kareem H. Al-Rubaiee, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Iraq is located near the northern end of the Arabian plate, which goes north relative to the Iranian plate, is expected to be an active tectonic country. During the past decade, seismic activity in Iraq has been observed to increase. Earthquakes are one of the disasters that cannot be accurately predicted with time, size, location, and intensity despite progress in seismic prediction. With the current state of scientific knowledge, it is difficult to predict when an earthquake will occur, although potential areas and expected magnitude are known based on seismic maps. Geotechnical earthquake engineering problems in civil engineering require characterization of dynamic soil properties using geophysical methods. The main objective of this study is to determine a data for the geotechnical and dynamical properties of different soil sites in Karbala City in Iraq using the results of drilling and seismic refraction survey method, and the seismic classification of those sites. From the collected results, it was observed that the shear wave velocities (Vs) were ranged from (300-420) m/s in the site of K.S.1, (280-450) m/s, in the site of K.S.2, respectively. While (450-540) m/s in the site of K.S.3. Karbala site soils are classified according to different seismic codes basing on Vs,30 value are the site soils are classified as types (D and C), according to the PISC and FEMA, while according to Eurocode 8: (C and B)